Efficacy and Safety of Ferrous Bisglycinate and Folinic Acid in the Control of Iron Deficiency in Pregnant Women: A Randomized, Controlled Trial - Bumrungpert, Akkarach; Pavadhgul, Patcharanee; Piromsawasdi, Theera; Mozafari, M. R. (Nutrients, 2022)
Iron deficiency in pregnancy is a major public health problem that causes maternal complications. The objective of this randomized, controlled trial was to examine the bioavailability, efficacy, and safety of oral ferrous bisglycinate plus folinic acid supplementation in pregnant women with iron deficiency. Subjects (12–16 weeks of gestation, n = 120) were randomly allocated to receive oral iron as ferrous bisglycinate (equiv. iron 24 mg) in supplement form with folinic acid and multivitamins (test group, n = 60) or as ferrous fumarate (equiv. iron 66 mg iron, control group, n = 60) after breakfast daily. Iron absorption was assessed by measuring fasted serum iron levels at 1 and 2 h immediately after supplementation. Hematological biomarkers and iron status were assessed before intervention, and at 3 and 6 months. Side effects were monitored throughout the intervention. A significant increase in serum iron was seen in both groups (p < 0.001) during the bioavailability assessment; however, the test group increases were comparatively higher than the control values at each timepoint (p < 0.001). Similarly, both test and control groups demonstrated a statistically significant increases in hemoglobin (Hb) (p < 0.001), erythrocytes (p < 0.001), reticulocytes (p < 0.001), mean corpuscular volume (MCV) (p < 0.001), mean corpuscular hemoglobin (MCH) (p < 0.001), mean corpuscular hemoglobin concentration (MCHC) (p < 0.001), % transferrin saturation (p < 0.001), and ferritin (p < 0.001) at 3 and 6 months after supplementation. However, in all cases, the test group increases were numerically larger than the control group increases at each timepoint. The test intervention was also associated with significantly fewer reports of nausea, abdominal pain, bloating, constipation, or metallic taste (p < 0.001). In conclusion, ferrous bisglycinate with folinic acid as a multivitamin nutraceutical format is comparable to standard ferrous fumarate for the clinical management of iron deficiency during pregnancy, with comparatively better absorption, tolerability, and efficacy and with a lower elemental iron dosage.